2019
DOI: 10.1039/c9ob01040h
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light mediated sulfonylation of thiols via insertion of sulfur dioxide

Abstract: Photocatalytically generated sulfenyl radicals were coupled with arylsulfonyl radicals at room temperature for accessing unsymmetrical organic thiosulfonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 59 publications
0
22
0
1
Order By: Relevance
“…Akshay M. Nair and co‐workers investigated aryl sulfonylation of thiols by treating thiophenol & DABCO ⋅ (SO 2 ) 2 with aryl diazonium salt at room temperature under photocatalytic conditions using eosin Y as a photocatalyst (Scheme 47). [72] Thiophenols bearing various functional groups such as methyl, methoxy, isopropyl, halogens, and naphthalene furnished the desired products in good yields under the optimized conditions. Notably, aliphatic thiols were also effective for this transformation and gave the expected products in good yields.…”
Section: C−s Bond Formationmentioning
confidence: 98%
“…Akshay M. Nair and co‐workers investigated aryl sulfonylation of thiols by treating thiophenol & DABCO ⋅ (SO 2 ) 2 with aryl diazonium salt at room temperature under photocatalytic conditions using eosin Y as a photocatalyst (Scheme 47). [72] Thiophenols bearing various functional groups such as methyl, methoxy, isopropyl, halogens, and naphthalene furnished the desired products in good yields under the optimized conditions. Notably, aliphatic thiols were also effective for this transformation and gave the expected products in good yields.…”
Section: C−s Bond Formationmentioning
confidence: 98%
“…In 2019, Volla and co-workers reported a protocol for the synthesis of thiosulfonates, via the three-component coupling of aryl diazonium salts, SO 2 , and thiols, mediated by visible-light photocatalysis ( Scheme 246 ). 640 Green-light irradiation of EY in the presence of thiol, aryl diazonium salt, and DABSO—the charge-transfer complex formed between DABCO and sulfur dioxide 641 —afforded 34 examples of thiosulfonate products in 54–89% yield. The authors demonstrated a wide scope of thiols, including thiophenols containing EWGs ( 246.1 ) and EWGs ( 246.2 ).…”
Section: S -Centered Radical Generation From S–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
“…This reaction proceeds via a radical-radial cross-coupling reaction promoted by an eosin Y photocatalyst under irradiation of visible light. 52…”
Section: Reviewmentioning
confidence: 99%